Dostopnost stanovanj in stanovanjska politika v Ljubljani - Mandič, Srna (Urbani izziv, 2007)
The focus of the article is on access to housing and the conceptual basis for its analysis and understanding in contemporary slovenian society. First the housing outcomes of the process of 'tranistion' are highlighted, still causing unfavourable conditions in the system of housing provision. This is followed by an overview of the discussion of housing deprivation, vulnerability and homelessness in the context of contemporary EU policy making. Finally the issue of housing deprivation is discussed in relation to the concept of 'welfare production', where the three sources of welfare are inter-related - the welfare state, the market and the family. The focus is onthe family and its role within popular housing strategies of the Slovenian population.
Keywords: dostopnost; družbena diferenciacija; Ljubljana; stanovanja; stanovanjska politika